Pengaruh Jumlah Penduduk, Pertumbuhan Ekonomi dan Ketimpangan Pendapatan terhadap Tingkat Kemiskinan di Provinsi Kalimantan Selatan Tahun 2003-2020 - Rasyid, Abdul; Sa’roni, Chairul (PPJP Universitas Lambung Mangkurat, 2023)
This research discusses the influence of Population Numbers, Economic Growth, and Income Inequality on Poverty rates in South Kalimantan Province in 2003-2020. This study aims to determine the impact of population, economic Growth, and income inequality on poverty levels in South Kalimantan from 2003-2020. This study used multiple linear regression analysis methods with specific time-lined data, and the data used operated with the E-Views 10 application. From the conclusion of the research that has been conducted, population effects negatively and significantly affect the poverty rate in South Kalimantan Province from 2003 to 2020. Economic Growth gives a negative and significant direction to the poverty rate in the Province of South Kalimantan in 20032020. At the same time, the Income Inequality variable had a positive but insignificant effect on the poverty level in the Province of South Kalimantan from 2003 to 2020.